Application of the Ulul Ilmi Model to Improve Critical Thinking and Religious Character in the 21st Century - Budiyanti, Nurti; Parhan, Muhamad; Komariah, Kokom Siti (Papanda Publisher, 2025)
This study aims to explore the implementation of the Ulul Ilmi Model in enhancing critical thinking skills and religious character among 21st-century students. A qualitative approach was used to development into the experiences and perspectives of students and educators in the application of this model. Data were collected through in- depth interviews, focus group discussions (FGD), and participatory observations. The participants in this study included students, teachers, and school staff who applied the Ulul Ilmi Model in their learning activities. The findings indicate that the application of this model is positive impacts the development of students ' critical thinking , reflected in their ability to analyze, evaluate, and solve problems more rationally. Additionally, this model too Strengths students ' religious character , as evidenced by an increase in spiritual awareness and moral values in their daily lives. This study concludes that the Ulul Ilmi Model can be an effective alternatives in 21st-century education to shape a generation that is not only intellectually intelligent but also has a strong religious character.